The rapid antidepressant effect of ketamine in rats is associated with down-regulation of pro-inflammatory cytokines in the hippocampus. (2nd October 2015) - Wang, Nan; Yu, Hai-Ying; Shen, Xiao-Feng; Gao, Zhi-Qin; Yang, Chun; Yang, Jian-Jun; Zhang, Guang-Fen
Abstract: Objectives. Active inflammatory responses play an important role in the pathogenesis of depression. We hypothesized that the rapid antidepressant effect of ketamine is associated with the down-regulation of pro-inflammatory mediators. Methods. Forty-eight rats were equally randomized into six groups (a control and five chronic unpredictable mild stress (CUMS) groups) and given either saline or 10 mg/kg ketamine, respectively. The forced swimming test was performed, and the hippocampus was subsequently harvested for the determination of levels of interleukin (IL)-1β, IL-6, tumour necrosis factor-α (TNF-α), indoleamine 2, 3-dioxygenase (IDO), kynurenine (KYN), and tryptophan (TRP). Results. CUMS induced depression-like behaviours and up-regulated the hippocampal levels of IL-1β, IL-6, TNF-α, IDO, and the KYN/TRP ratio, which were attenuated by a sub-anaesthetic dose of ketamine. Conclusion. CUMS-induced depression-like behaviours are associated with a reduction in hippocampal inflammatory mediators, whereas ketamine's antidepressant effect is associated with a down-regulation of pro-inflammatory cytokines in the rat hippocampus.